Innovations towards sustainable olive crop management: a new dawn by precision agriculture including endo-therapy - Grandi, Luca; Oehl, Michael; Lombardi, Tommaso; de Michele, Vito Rocco; Schmitt, Nicolas; Verweire, Dimitri; Balmer, Dirk (Frontiers in Plant Science, 2023)
Olive trees (Olea europaea L.) are deeply interwoven with the past, present and future of Mediterranean civilizations, both as essential economical as well as cultural valuables. Olive horticulture constitutes one of the primary agroecosystems in the Mediterranean regions of today. Being inhabitant of ecological niches, Olea europaea is prone to a peculiar vulnerability towards climatic and socioeconomical transformations that are briskly reshaping regional and global agroecosystems. Because of climatic changes and the biosafety risks of global agricultural trades, olive plants are highly susceptible to newly emerging diseases and pests, and the traditional olive horticultural crop protection practices are under scrutiny towards reducing their ecological impact. Hence there is an eminent demand for a more nature-positive olive tree crop management. Recent innovations in precision agriculture are raising the prospect for innovative crop protection methods that may provide olive farmers the required agility to respond to present and future agricultural challenges. For instance, endo-therapy, which is the systemic delivery of active ingredients via trunk injection, is a technology that holds promise of a true step-change in sustainable olive crop management. Endo-therapy allows reaching vascular diseases inaccessible to foliar treatments and delivers active ingredients in a precise manner with no risks of off-target drifts. Similarly, progresses in biological precision delivery using controlled release of active ingredients based on innovative formulation technologies are showing an exciting potential for more targeted and sustainable crop protection solutions. This review summarizes the latest innovations on both physical and biological precision deliveries in the realm of olive arboriculture in the Mediterranean regions and gives an outlook how these technologies may help orchestrating innovative olive culture practices soon.